Peran Pemerintah Kabupaten Deli Serdang Dalam Meningkatkan Pembangunan Ekonomi Daerah Melalui Sektor Pariwisata - Bintang Akbar Azhari; Imsar Imsar (Jurnal Akuntansi AKTIVA, 2023)
This research aims to describe and analyze the role of the Deli Serdang Regency Government in increasing development in the regional economy through the tourism sector (case study on Bali Lestari Beach, Percut Sei Tuan District). This research uses the qualitative methods. And the results of this study, show that in developing or improving regional economic development in the tourism sector, the Deli Serdang Regency Government has carried out its role as an entrepreneur and coordinator to the maximum in order to improve economic development. Although in reality, it is not very perfect there are still obstacles, obstacles but the Government and Movers / members of Pantai Bali Lestari will continue to strive to overcome the problems that will occur.